2022
DOI: 10.3390/agriculture12081115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Harvesting Period and Storage Duration on Volatile Organic Compounds and Nutritive Qualities of Alfalfa

Abstract: Harvest time and storage time had significant effects on nutrient quality and Volatile Organic Compounds (VOCs) of alfalfa. The objective of this study was to use headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS) to analyze alfalfa at different harvest periods (budding stage, early blooming, full blooming), and storage for 0 d, 90 d, 180 d, 270 d, and 360 d, the dynamic changes in VOCs and nutritional quality. Results indicated that ketones, aldehydes, alcohols and este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A study was conducted to analyze alfalfa at different harvest periods and storage periods to assess the dynamic changes in the VOCs and nutritional quality levels. The results indicated that the VOCs and nutrient quality of alfalfa varied significantly in different harvest periods; delayed harvesting significantly reduced a range of different nutrient levels (Yuan et al, 2022). The accumulation of five major saponins in three harvest seasons of Panax notoginseng was detected by HPLC, and it was found that September in the third year was the best harvesting time due to the highest content of these five major saponins in the roots at that time (Xia et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…A study was conducted to analyze alfalfa at different harvest periods and storage periods to assess the dynamic changes in the VOCs and nutritional quality levels. The results indicated that the VOCs and nutrient quality of alfalfa varied significantly in different harvest periods; delayed harvesting significantly reduced a range of different nutrient levels (Yuan et al, 2022). The accumulation of five major saponins in three harvest seasons of Panax notoginseng was detected by HPLC, and it was found that September in the third year was the best harvesting time due to the highest content of these five major saponins in the roots at that time (Xia et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…This can be attributed to the vegetative growth stage of the alfalfa plant, characterized by its rapid growth and nutrient accumulation. Yuan et al [ 30 ] posit that the optimal period for harvesting alfalfa is during the bud stage, and early harvested purple alfalfa exhibits lower fiber content but higher CP content. Delaying the harvest lowers the quality of purple alfalfa, which aligns with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the vegetative growth stage of the alfalfa plant, characterized by its rapid growth and nutrient accumulation. Yuan et al [30] posit that the…”
Section: Chemical Composition Of Alfalfa Raw Materials Before Silagementioning
confidence: 99%
See 1 more Smart Citation
“…In alfalfa, the stem base is not merely a physical junction, but a vital hub of resilience, underpinning the plant’s remarkable ability to recover and regenerate [ 13 ]. This key area not only enables alfalfa to withstand environmental stressors and adverse conditions, but also supports its capacity to regrow vigorously after dormancy or harvesting [ 14 ]. These factors collectively influence the plant’s viability, productivity, ability to overwinter successfully, and the overall quality of the forage it produces [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%